Genatic variability and characterisation in wax type chilli (capsicum annuum L.) - Mini S (Department of Plant Breeding and Genetics, College of Agriculture, 2003)
The present study entitled “Genetic variability and characterisation in wax type chilli (Capsicum annuum L.). was conducted at the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani, Thiruvananthapuram, during 2002-2003. The data for investigation was collected from a field experiment laid out in Randomised Block Design (RBD) with three replications. The 25 genotypes included in the study showed significant difference for the 14 traits. The maximum values for phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) were recorded for green fruit yield per plant and the minimum values for number of days to first flowering. PCV and GCV were high for fruit yield, number of fruits per plant, average fruit weight, 100-seed weight and fruit length. Fruiting span, 100-seed weight, fruit length, average fruit weight, number of fruits per plant, fruit yield per plant and number of secondary branches showed high heritability coupled with high genetic advance. Yield per plant was positively correlated with plant height, average fruit weight, number of fruits per plant, fruit width, 100-seed weight, number of primary branches, number of secondary branches, plant spread and fruit length. Path analysis revealed high positive direct effects of number of fruits per plant and average fruit weight with yield. Hence selection for these characters can improve yield. The 25 genotypes were grouped into nine clusters based on Mahalanobis D2 statistic. Cluster II was the largest with seven genotypes while cluster VIII and IX with one genotype each were the smallest. Intercluster distance was maximum between III and IX while intracluster distance was maximum in VII. Cluster III containing three genotypes and cluster VIII containing a single genotype was found to be superior to the other clusters in respect of desirable characters. The genotypes also obtained high ranks when ranked on the basis of selection index. Morphological characterisation of the genotypes with respect to six morphological traits viz., Plant growth habit, branching, leaf density, fruit shape, fruit surface and fruit cross sectional corrugation was also done. The high yielding types viz., Honnavar Local, Payyannur local, Periya local, Para local and Hungarian Wax identified from the study could be used as parents in crop improvement to evolve high yielding varieties.